Perlindungan Hukum bagi Pedagang Mobil Bekas terhadap Konsumen yang Melakukan Wanprestasi - Bagus Putu Lanang Agastya; Anak Agung Sagung Laksmi Dewi; Ni Made Puspasutari Ujianti (Warmadewa Press, 2020)
The sale and purchase of expertise in contract law regarding the terms of the legality of the agreement and all the provisions in the legal agreement governing the sale and purchase activities and protecting the parties from default regarding the rights and obligations of each party. The purpose of this study is to determine the form of legal protection regulations for used car dealers against consumers who default and respond to the law for consumers who default. This study uses a normative method. The data analysis technique was carried out systematically using legal arguments and presented in a descriptive form. The results showed that in order to protect the parties from a default, it is necessary to have an agreement that is binding in nature and each of them has rights and obligations if it is violated, it will set a sanction in accordance with the agreement made in general in the form of compensation. Meanwhile, the result of default by the consumer must be responsible and compensate according to the agreement between the two parties. Therefore, through this research it is hoped that trade activities are carried out and implement the importance of agreements and pay attention to all requirements in the law. The goal is to protect yourself from unwanted events.